2022
DOI: 10.31004/basicedu.v6i5.3643
|View full text |Cite
|
Sign up to set email alerts
|

Analisis Kemampuan Penalaran dalam Soal Pemecahan Masalah Matematika Ditinjau dari Self-Confidence melalui Model Pembelajaran Discovery Learning

Abstract: Kemampuan penalaran dalam proses pembelajaran matematika sangatlah dibutuhkan untuk semua para siswa,  dengan kemampuan penalaran yang dimiliki akan membantu siswa dalam menyelesaikan setiap permasalahan yang ada. Sehingga tujuan penelitian ini adalah mendeskripsikan kemampuan penalaran matematis siswa pada materi aritmetika sosial melalui model pembelajaran Discovery Learning. Desain penelitian ini adalah mixed method tipe concurrent embadded dengan penelitian kuantitatif sebagai primer untuk memperoleh data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 9 publications
0
1
0
Order By: Relevance
“…Results in a mixed study using the DL/IL model revealed an increase ability reasoning mathematical on class with learning models discovery learning more tall from on class normal (Santana et al, 2022) . Furthermore, for PTK research using the DL/IL model, it shows that students' mathematical reasoning abilities increased from cycle I to cycle II (Jabar & Lestari, 2018;Parida et al, 2020;Tukaryanto et al, 2018) .…”
Section: Figure 2 Total Of Articles By Year Of Publicationmentioning
confidence: 99%
“…Results in a mixed study using the DL/IL model revealed an increase ability reasoning mathematical on class with learning models discovery learning more tall from on class normal (Santana et al, 2022) . Furthermore, for PTK research using the DL/IL model, it shows that students' mathematical reasoning abilities increased from cycle I to cycle II (Jabar & Lestari, 2018;Parida et al, 2020;Tukaryanto et al, 2018) .…”
Section: Figure 2 Total Of Articles By Year Of Publicationmentioning
confidence: 99%
“…Mathematical reasoning is the foundation for obtaining or constructing mathematical knowledge, while mathematics is a means of thinking to examine something logically (Santana, Sunarso, & Mariani, 2022). The importance of mathematical reasoning abilities greatly influences the mathematics learning process they follow.…”
Section: Introductionmentioning
confidence: 99%
“…The importance of mathematical reasoning abilities greatly influences the mathematics learning process they follow. Because students who have good reasoning abilities will easily understand mathematical material, and contrary; students with low mathematical reasoning abilities will find it difficult to understand mathematical material (Santana, Sunarso, & Mariani, 2022). The statement formulated by the Ministry of National Education in 2002 (Nasional, 2002) states Mathematical matter and reasoning are two things that cannot be separated.…”
Section: Introductionmentioning
confidence: 99%